Numerical study of a combined wind turbine blade - Bashirov, M.K.; Kyzdarbekova, Sh.S.; Tanasheva, N.K.; Dyusembaeva, A.N. (Karagandy University of the name of academician E.A. Buketov, 2025)
This article is devoted to a numerical study of the power elements of Magnus wind turbines. The improved blade shape is made in the form of a combination of a cylindrical element with a fixed blade, which helps to in crease overall efficiency and increase the lifting force of the power element. The aerodynamic coefficients of a combined blade are investigated depend ing on the angle of the fixed blade in the range from 0° to 60°. It is deter mined that the maximum lifting coefficient reaches 1.2 at an angle of 0°. With this angle value, there is also a minimum value of the coefficient of drag force equal to 1.5. Based on the data obtained, the optimal angle of the fixed blade is from 0° to 30°.
Keywords: wind turbine; numerical study; combined blade; ANSYS Fluent; aerodynamic coefficients